Gold price: Long-run and short-run determinants - Dinh, Trung Duc (2010)
This dissertation aims to examine the long-run and short-run relationships between gold price and its determinants. Monthly data and OLS regression techniques are used to develop two empirical models, one for long-run relationships and one for short-run relationships. We find that in the long-run, gold price is fairly stable and raises in line with US general price level. However the relationship is not a one-for-one relationship. Thus gold is not an effective hedge against US inflation. In addition, we find that short-run changes in the dollar/world exchange rate can disturb the long-run relationship and generate short-run price volatility. This paper also investigates the effects of one of the biggest financial crisis, namely sub-prime crisis, on the long-run as well as short-run relationships. It is the first attempt to do it. We find that under the effects of the crisis, the positive long-run relationship between gold price and US general price level is still kept. But the relationship becomes closely a one-for-one relationship. Thus gold is more effective in hedging against US inflation. Furthermore, we find that the short-run relationships generally are affected substantially by the crisis, except the negative relationship between dollar/world exchange rate and gold price. Under effects of the crisis, the movements in short-run price of gold are caused by short-run changes in US/world exchange rate index, US inflation, US inflation volatility, and gold beta.